Perilaku Kewargaan Organisasi Bagi Guru Untuk Meningkatkan Kinerja Profesi Keguruan - Ginting, Desy Brema Sevriani; Ivanna, Julia; Nababan, Ramsul (Jurnal Kewarganegaraan, 2021)
AbstractThe teacher is the most important factor in the field of education, because the teacher is the driving force of education for students in achieving educational goals. If there is a managerial role from the leader, the teacher will be able to teach the school the best. Therefore, the principal must be able to motivate teachers to improve teacher performance. This article aims to determine the performance of OCB (Organizational Citizenship Behavior) in teacher leadership and integrity. This article uses the literature study method. Therefore, the principal must be able to stimulate teachers to improve their performance. The method used is descriptive analysis. __________ AbstrakGuru adalah faktor yang terpenting dalam bidang pendidikan, karena guru adalah penggerak pendidikan bagi siswa mencapai tujuan pendidikan. Dalam hal peran manajerial dari pemimpin maka guru akan mampu melakukan pengajaran yang terbaik sekolah. Oleh karena itu, kepala sekolah harus mampu memotivasi guru dalam meningkatkan kinerja guru. Artikel ini bertujuan untuk mengetahui kinerja perilaku kewargaan organisasi dalam kepemimpinan dan integritas guru. Artikel ini menggunakan metode studi kepustakaan. Karena itu, kepala sekolah harus bisa merangsang guru untuk meningkatkan kinerjanya.